Synthesis of a Novel Fluorescent Ruthenium Complex with an Appended Ac4GlcNAc Moiety by Click Reaction - Qi Cheng; Yalu Cui; Nao Xiao; Jishun Lu; Chen-Jie Fang (Molecules, 2018)
The O-linked β-N-acetylglucosamine (O-GlcNAc) modification is an abundant post-translational modification in eukaryotic cells, which plays a fundamental role in the activity of many cells and is associated with pathologies like type II diabetes, Alzheimer’s disease or some cancers. However, the precise connexion between O-GlcNAc-modified proteins and their function in cells is largely undefined for most cases. Confocal microscopy is a powerful and effective tool for in-cell elucidation of the function of biological molecules. Chemical labeling of non-ultraviolet or non-fluorescent carbohydrates with fluorescent tag is an essential step that makes intra-cellular microscopic inspection possible. Here we report a strategy based on the 1,3-dipolar cycloaddition, called click chemistry, between unnatural N-acetylglucosamine (GlcNAc) analogues Ac4GlcNAc (substituted with an azido group) and the corresponding fluorescent tag Ru(bpy)2(Phen-alkyne)Cl2 (4) to synthesize the fluorescent dye Ru(bpy)2(Phen-Ac4GlcNAc)Cl2 (5) under mild and neutral reaction conditions. Moreover, 5 showed good stability, desirable fluorescence characteristics, and exhibited rather low levels of cytotoxicity against sensitive MCF-7 cells. Additionally, we have achieved successful fluorescent imaging of 5 transported in living MCF-7 cells. Cell images displayed that proteins are potentially labelled with 5 in the cytoplasm.